Approaching moisture recycling governance. (July 2017) - Keys, Patrick W.; Wang-Erlandsson, Lan; Gordon, Line J.; Galaz, Victor; Ebbesson, Jonas
Highlights: Governance of atmospheric moisture recycling is an Anthropocene governance gap. Vegetation evaporates moisture that forms rainfall, which often falls in other countries. Different types of moisture exchange require different governance principles. Atmospheric moisture exchange among countries is categorized into four types. Moisture recycling can partly be integrated into existing governance approaches. Abstract: The spatial and temporal dynamics of water resources are a continuous challenge for effective and sustainable national and international governance. The watershed is the most common spatial unit in water resources governance, which typically includes only surface and groundwater. However, recent advances in hydrology have revealed 'atmospheric watersheds' – otherwise known as precipitationsheds. Water flowing within a precipitationshed may be modified by land-use change in one location, while the effect of this modification could be felt in a different province, country, or continent. Despite an upwind country's ability to change a downwind country's rainfall through changes in land-use or land management, the major legal and institutional implications of changes in atmospheric moisture flows have remained unexplored. Here we explore potential ways to approach what we denote as moisture recycling governance. We first identify a set of international study regions, and then develop a typology of moisture recycling relationships within these regions ranging from bilateral moisture exchange to more complex networks. This enables us to classify different types of possible governance principles and relate those to existing land and water governance frameworks and management practices. The complexity of moisture recycling means institutional fit will be difficult to generalize for all moisture recycling relationships, but our typology allows the identification of characteristics that make effective governance of these normally ignored water flows more tenable.